The shaping of milk-flavored white tea: More than a change in appearance - Jiao Feng; Weisu Tian; Jinyuan Wang; Shuping Ye; Guanjun Pan; Bugui Yu; Fang Wang; Hongzheng Lin; Zhilong Hao (Journal of Integrative Agriculture, 2024)
Tea's popularity and flavor are influenced by factors like cultivation and processing methods and shaping techniques also have an impact on tea flavor. This study employed targeted metabolomics and chemometrics to investigate how shaping techniques affect the flavor of milk-flavored white tea (MFWT). The results showed that the tea cake sample with the shortest pressing time (Y90) has the highest amino acid content and milky aroma intensity. There were variations in amino acids, catechins, and soluble sugars among MFWT samples with different shaping techniques. The total contents of amino acids and catechins in tea cake sample (Y90) were significantly lower than those in the loose tea sample (SC) and bundle-like tea sample (SG), while the total sugar content was significantly higher than that in SC (P<0.05). Additionally, the content of volatiles presenting milky aroma (VIP&OAV>1) in Y90 remained lower relative to SC and SG (P<0.05), but the proportion was not different from that in SC and SG, minimally affecting the overall flavor. The short-time pressing method might be suitable for mass production of MFWT. These findings provide insights into improving the tightness of the appearance of MFWT with minimal impact on tea flavor.